Stakeholders’ Institutional Roles in a Contemporary Barter Exchange System in Bulgarian Municipality - Toncheva, Rossitsa (Research Papers, 2021)
This study presents a long-standing research of contemporary barter exchange systems, the logical continuation of which is a scientific project of UNWE. The purpose of the analysis is the main position of stakeholders for taking part in the organization and operation of a contemporary barter exchange systems in the Bulgarian municipality to be highlighted. In addition to outlining the problem in the multilateral study (evolution in terminology and design of all stakeholders’ behavior, grouped according to their specific roles), a number of clarifications are made, including additional arguments used as a focus on the subject of the research. The object is the conceptual construction of the contemporary barter exchange systems together with its main element, which manifests it – “private non-bankc money”, both as a holistic entity. The subject is the interests and roles of potential participants in this system, primarily at the level of Bulgarian municipality. It has been considered the opinion that private non-bankc money could be applied as an useful tool not only for reducing the severity of systemic crises that the traditional financial order regularly creates, but also as a countermeasure to external shocks of various kinds, including measures to limit Covid-19, which forever changed the economic and social reality all over the world.